ตัวแบบการตัดสินใจซื้อความจุที่ว่างของเที่ยวรถที่บรรทุกไม่เต็มคันเพื่อขายต่อ - วิษณุ สามเมือง (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
Trips of empty trucks and less-than-truckload trucks are wasteful and make truck owners willing to sell the unused capacities at lower prices than usual hauls. This research presents a concept of managing trips of empty or less-than-truckload trucks in the business of a third-party entrepreneur who purchases unused capacities in some trips from truck owners to service customers who want to transport their cargos at lower than usual costs. It also presents models for setting the target capacities to purchase and sell for each route in each period in order to support the decision to accept or reject the offer to sell the unused capacity in a truck trip and the decision to accept or reject the requests for service. Occurrences of offers are uncertain and the objective in decision making is to maximize the expected profit with consideration on costs incurred from insufficient and excessive purchased capacity. A program was developed on the decision models to simulate and test 30 problems. The results under the controlled parameters indicated that the decision model generated on average 37.43% profit to the third-party entrepreneur.